AEC Blueridge Alpine bluegrass - Darroch, B. A.; Acharya, S. N. (Canadian Journal of Plant Science, 1996)
AEC Blueridge alpine bluegrass (Poa alpina L.) is a reclamation variety developed for use in reclaiming and revegetating disturbed sites at high elevations. It is the first variety of alpine bluegrass released in Canada. Its primary advantage over varieties of other bluegrass species is its ability to thrive under the harsh environmental conditions found at high elevations. Key words: Cultivar description, AEC Blueridge Alpine bluegrass